2016
DOI: 10.1128/aac.01016-16
|View full text |Cite
|
Sign up to set email alerts
|

First Occurrence of OXA-72-Producing Acinetobacter baumannii in Serbia

Abstract: e Here, we characterized the first OXA-72-producing Acinetobacter baumannii isolate (designated MAL) recovered from a urine sample from a Serbian patient. Antimicrobial susceptibility testing, plasmid analysis, and whole-genome sequencing (WGS) were performed to fully characterize the resistome of the A. baumannii MAL clinical isolate. The isolate was multidrug resistant and remained susceptible only to colistin and tigecycline. PCR analysis revealed the presence of the carbapenemase OXA-72, an OXA-40 variant.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 40 publications
3
13
1
Order By: Relevance
“…The pAB-MAL-2 plasmid was found circulating in both the Tn2006-and the pMAL-1-linked outbreak clones. pAB-MAL-2 detected in this study was slightly different from that in previous reports (26). The plasmid was additionally positive for a TA system showing 60% similarity to a recently described higBA2 Ab TA module on pAB120 (27).…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…The pAB-MAL-2 plasmid was found circulating in both the Tn2006-and the pMAL-1-linked outbreak clones. pAB-MAL-2 detected in this study was slightly different from that in previous reports (26). The plasmid was additionally positive for a TA system showing 60% similarity to a recently described higBA2 Ab TA module on pAB120 (27).…”
Section: Discussioncontrasting
confidence: 96%
“…bla OXA-72 was first identified in 2004 in A. baumannii isolated from Taiwan, and since then it was detected in a few other countries, including Brazil, France, and the United States (36). The pMAL-1 plasmid was very similar to p2ABST25, with the latter being negative for ISAba31 (26). The presence of ISAba31 upstream of bla OXA-72 has been reported previously in pMAL-1 (26), yet its effects on bla OXA-72 expression require further investigations.…”
Section: Discussionmentioning
confidence: 97%
“…21,22 BlaADC-25 is a chromosomally encoded cephalosporinase that typically confers resistance to all β-lactams. 23 Our results showed that there are no identified mutations that could account for change in function of blaOXA-91, matching our susceptibility testing. However, six non-synonymous mutations identified in blaADC-25 could potentially change the enzymatic activity of this β-lactamase.…”
Section: Discussionsupporting
confidence: 81%
“…Forty nine Class D (OXA) β-Lactamases have also been described from A. baumannii; 4 of them -(OXA-239, OXA-72, OXA-51, and OXA-253) -were discovered or re-described in the last year [165][166][167][168][169][170].…”
Section: β-Lactamasesmentioning
confidence: 99%